POLITICAL SCIENCE EDUCATION IN NIGERIA: AN IMPERATIVE TOOL FOR SUSTAINABLE DEVELOPMENT - Kwasau, Muhammad Aminu (European Scientific Journal, ESJ, 2013)
Political Science Education concerns with the study and analysis of the theories, Institutions and processes of political systems and their functions within complex societies. The field examines the structures of governments and their historical evolution over time as well as the question of how governmental authority is established and maintained in different eras and different societies. The discipline also acquaints students with the methods of teaching political science in tertiary institutions or Government in Secondary Schools. This paper has been divided into six main sections. Following the introduction is the conceptual clarification. Part three discusses the methods of teaching political science. The fourth segment of the paper examines the relevance of political science education in achieving sustainable development. Section five highlights the problems and challenges of political science education in Nigeria. The last segment of the paper is the recommendations and conclusion.